saifoal7elo
saifoal7elo
04-09-2020
SAT
contestada
If f(x)=x+1 and g(x)= 3x+4 then f(g(2)) - g(f(2))=
Respuesta :
amoleh25
amoleh25
05-09-2020
g(2) = 3(2) + 4
g(2) = 10
f(2) = (2) + 1 = 3
g(3) = 3(3) + 4 = 13
f(10) = (10) + 1 = 11
11 - 13 = -2
Final Answer: -2
Answer Link
VER TODAS LAS RESPUESTAS ( 32+ )
Otras preguntas
20 homographs in pairs
The harmful effects of tobacco use are mainly caused by what substances? nicotine, tar, carbon dioxide nicotine, tar, carbon monoxide opium, alcohol, carbon mon
are all proteins enzeims
enforce is to impose as feud is to?
Convert the fraction to higher terms. Enter the value of the missing numerator. 3/11= /77?
I need help with numbers 5,6, and 7
Which word does NOT refer to a liquid ? a. allude b. deluge c. imbibe d. potable
Maria is reading an essay comparing two poems and has come across a missing word. A love poem by a Classicist will express emotion in a logical and restrained
A response that is automatic, or not learned, is called a conditioned response. a. True b. False
A major obstacle to developing good human relations skills is that a. few persons have common interests. b. people fear taking risks. c. common interests won